$3.20
2.99 • 7% = 0.2093
2.99 + 0.2093 = 3.20
Answer:
The correct option is option B. It has one solution, and it's x=-3
Step-by-step explanation:
We have the following system of equations:
5x+7 = 2y (1)
y-9x=23 (2)
Step 1: Solve for 'y' in equation (2):
y-9x = 23
y = 9x + 23
Step 2: Substitute in equation (1):
5x + 7 = 2y
5x + 7 = 2(9x + 23)
5x + 7 = 18x + 46
Step 3: Solve for x:
7 - 46 = 18x - 5x
-39 = 13x
x= -3
So the correct option is option B. It has one solution, and it's x=-3
Answer:
x^2+7x+10
Step-by-step explanation:
multiply the first by first and first by second
multiply the second by first and second by second